GAYA BELAJAR SISWA BERPRESTASI AKADEMIK PADA KELAS V DI SEKOLAH DASAR NEGERI 02 KECAMATAN SABAK AUH KABUPATEN SIAK - Eling Sutriani; Syahrilfuddin Syahrilfuddin; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is made to describe the learning methods that students with academic achievements usually do and the mostcommon learning style used by students with academic achievements have on fifth grade at SD Negeri 02 Bandar Sungai.The subjects of the research itself are student of first, second and third grade who have academic achievement. This researchis a qualitative research. The data collecting process is held through observations, interviews and documentations. Dataanalyst in this research is using Milles and Huberman data analysis technique, the process itself is done through cpllectig,reducing, displaying and taking conclusion. This research going through creadibility test, dependsbility, and confirmation togain data validation. The result of the research shows that students learning methods on fifth grade students of SD Negeri 02Bandar Sungai is the combination of vak learning methods. The tedency of student’s learning methods is various, the firstgrade students would prefer visual, second grade students prefer auditorial, and third grade students choose kinectical wayof learning. From data collecting exhibits, none of theree achievers students use one learning method in majority. Herewith,in this research the way of learning as may weel said as learning methods don’t affect student’s academic achievements.There are others indicators to it . That for instance, parent encouragement, teacher teaching methods, students learningenvironment, interes and genetic that runs in the family.